The Effect of Personality Traits and Learner Engagement on L2 Motivated Behavior of Undergraduate Students - Khalid, Tabeer; Islam, Muhammad (Annals of Human and Social Sciences, 2024)
The paper aims to see the effect of Personality Traits and Learner Engagement on L2 Motivation of 600 undergraduate students from Lahore, Pakistan, Using a quantitative method and an ex post facto design. The data was collected through an adapted questionnaire. Descriptive statistics and inferential statistics findings have shown that both Personality Traits and Learner Engagement effect L2 Motivation significantly. The Personality Traits have shown a 26% variance and Learner Engagement has shown a 58% variance with L2 Motivation. Further, the Personality Traits of ‘Extraversion, Conscientiousness, and Openness’ significantly effect L2 Motivation. Similarly, all three forms of learner engagement used in this study show a significant effect on L2 motivated behavior of participants. Future studies may focus on younger students, e.g. higher secondary-level, to analyse how personality traits and engagement of these children may be useful in predicting their L2 motivation.